A new Sarcophaginae (Diptera: Sarcophagidae) from Brazil: the peculiar colour of Petrolina bifasciata gen. nov., sp. nov., from the Caatinga xeric shrubland of northeastern Brazil - Barbosa, Taciano Moura; Mello-Patiu, Cátia Antunes; Vasconcelos, Simão Dias (Zootaxa, 2023)
A new genus and species, Petrolina bifasciata gen. nov., sp. nov. (Diptera: Sarcophagidae, Sarcophaginae), with only two black stripes dorsally on thorax, is described from both sexes. The type material was collected in fragments of seasonally dry tropical forest in the state of Pernambuco, northeastern Brazil. The new genus and species is morphologically similar to genera Rafaelia Townsend and Malacophagula Bequaert. However, the atypical two thoracic black stripes and phallic morphology give evidence to the proposal of a new genus in Sarcophaginae.